Phylogenetic signal in the topographic niche of trees: Current and historical significance of habitat structure on the species arrangement pattern within East Asian rugged forests. Issue 4 (22nd May 2020) - Kitagawa, Ryo; Mimura, Makiko; Mori, Akira S.; Sakai, Akiko
Abstract: Topography often promotes habitat heterogeneity and is a major factor in fine‐grained changes in vegetation. Especially in temperate mountainous regions of East Asia, the distribution of tree species is largely explained by topographic niche differentiation. Because species niche is at least partially a historical product through the evolution of functional traits, phylogenetic signals are expected in the topographic arrangement pattern of species, although this has not been fully investigated. Thus, we examined common temperate trees in a 306 ha watershed on Mt Tanzawa, central Japan. The topographic niche position of each species was explained with two principal component analysis (PCA) axes, which aligned with the topographic structure of the watershed. High scores on PC1 reflected lower elevations, steeper slopes and nearby valleys. Higher scores on PC2 indicated thicker soil, more south‐facing slopes, slighter slope inclinations and nearby valleys. The former indicated the species were aligned on a habitat gradient of land‐surface instability, for which the gradient is typical under the current geological conditions. The latter indicated that a niche axis for resource availability relating to water, nutrients and light or heat existed. A phylogenetic signal, identified by Pagel's λ and the Mantel test, was detected for PC2 scores. However, the species arrangement along PC1 was independent of phylogeny. Our results suggested that the topographic niche of tree species in this area is caused by both relatively recently derived traits regarding adaptation to unstable land surfaces and conservative traits derived through plant evolution. Abstract : In this article, we try to link the actual pattern of niche differentiation that can be observed in the fields to biogeographical histories. Based on the results, we discussed the evolutional and biogeographical history of the fine‐scale topographical niche differentiation in the mountainous forests of the coastal areas of East Asia.